Die Missionsstation Makkovik von zugefrorener Bucht aus : [ca. 1901] - Schmitt, Christian, 1868-1933. (2001)
Black and white photograph of a view of the Moravian church and mission building at Makkovik from the frozen bay, circa 1901. Black and white photograph of a view of the Moravian church and mission building at Makkovik from the frozen bay, circa 1901.